THE ANALYSIS OF TEACHER AND STUDENTS TALK IN INDONESIAN EFL CLASSROOM INTERACTION - Shilvia Nur Meida; Fahrus Zaman Fadhly (Indonesian EFL Journal, 2018)
This research analyzes teacher and students talk in Indonesian EFL classroom interaction in University of Kuningan in second semester who are taking Speaking 2 subject. This qualitative data was from observation, note taking, and interview. The result of classroom observation found the content cross as the most dominant characteristic in teacher and students talk, it means that most of the teaching learning process devoted to asking questions and lecturing by the lecturer. The proportation of content cross was 65.55% in the first meeting, 95.88% in the second meeting, and 97.44% in the third meeting. While, in the additional data, the most dominant category found was teacher talk. It means that all of teacher talk categories appear in each meeting. The proportation of teacher talk is 38.16% in the first meeting, 55.11% in the second meeting, and 54.83% in the third meeting. In addition, the result of note taking and interview indicated that the interaction always happened in teaching learning process among students although the lecturer’s role is still dominant.Keywords: teacher and students talk, FIAC analysis system, speaking skill